2017
DOI: 10.12659/msm.905510
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Otologic Symptoms and Evaluation of the Organ of Hearing in Patients with Temporomandibular Disorders (TDM)

Abstract: BackgroundNumerous studies have discussed cases of concomitant temporomandibular disorders (TMD) and otologic symptoms (OS). However, attempts to determine the true origin of these symptoms combined with assessments of the condition of the organ of hearing are relatively rare.This study aimed to evaluate the frequency and type of OS in patients with TMD, and attempted to determine the origin of the OS in the studied group of patients.Material/Methods246 patients, aged 40.08±11.12 years (F=147, M=99) with TMD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…Maciejewska‐Szaniec et al demonstrated that in a cohort of 246 patients with TMJD, 36% of patients had abnormal audiologic testing. Twenty‐seven percent of these patients had conductive hearing loss, and 12% had mixed hearing loss, perhaps suggesting middle ear dysfunction . Unfortunately, although the study notes that all patients underwent impedance audiometry, these results were not reported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Maciejewska‐Szaniec et al demonstrated that in a cohort of 246 patients with TMJD, 36% of patients had abnormal audiologic testing. Twenty‐seven percent of these patients had conductive hearing loss, and 12% had mixed hearing loss, perhaps suggesting middle ear dysfunction . Unfortunately, although the study notes that all patients underwent impedance audiometry, these results were not reported.…”
Section: Discussionmentioning
confidence: 97%
“…Twenty-seven percent of these patients had conductive hearing loss, and 12% had mixed hearing loss, perhaps suggesting middle ear dysfunction. 23 Unfortunately, although the study notes that all patients underwent impedance audiometry, these results were not reported. Porto De Toledo et al performed a systematic review and meta-analysis on the prevalence of otologic signs and symptoms in patients with TMJD, and in their review of eight studies found that otologic symptoms were quite common: ear fullness (74.8%), otalgia (55.1%), tinnitus (52.1%), vertigo (40.8%), and hearing loss (38.9%).…”
Section: Discussionmentioning
confidence: 99%
“…4 Kulak semptomları değerlendirilirken bazı çalışmalarda odyolojik testlerden faydalanılmıştır. 4,9,26 Bazı çalışmalarda da hastalara kulak semptomları var veya yok şeklinde formlar doldurularak yapılmıştır. 1,3,10 Bizde Akhter ve ark.…”
Section: Gereç Ve Yöntemunclassified
“…The method of classifying individuals as those with and without tinnitus and with and without TMDs was quite different. To diagnose patients with TMDs, 1 papers used RDC/TMD 11,12,18,33,36,37,39,40,42 or its revised versions, 7,31 6 papers did clinical examinations, 28,29,35,38,41,43 3 asked some questions, 32,34,44 and 2 used both clinical examinations and asking questions. 16,30 The method of labeling patients as those suffering from TMDs was summarized in Tables 1 and 2.…”
Section: Findings From the Systematic Reviewmentioning
confidence: 99%
“…Two publications used a question in RDC/TMD questionnaire. 36,39 Other studies asked 1 or more questions, 7,11,12,18,[28][29][30][31][32][33][34]37,38,40,[42][43][44] but the applied questions were only mentioned in 4. [28][29][30]33 The tinnitus handicap inventory (THI) questionnaire was used in 3 papers.…”
Section: Instrumentationmentioning
confidence: 99%